(untitled) (Journal of Human Sciences, 2024)
This study aimed to explore the Negritude and Afrocentrism movements, identify their most prominent leaders, and examine the historical conditions and motivations that led to their emergence. It also investigated their vital role in critiquing the racist colonial experience and in challenging the negative stereotypes imposed on African peoples by the exclusionary Western-centric ideology and its colonial discourse. Furthermore, the study highlighted the efforts to cultivate African liberation consciousness, achieve independence and unity, and lay the foundation for African intellectual, political, and literary perspectives that address the concerns of the African people and express their aspirations for freedom and emancipation, free from the exclusion and marginalization they have endured for a long time.